Synthesis and electronic properties of transition metal complexes containing sulfonamidoquinoline ligands. (1st September 2021) - Gole, Matthew T.; Pauls, Patrick; Hartlaub, Sage F.; Nataro, Chip; Rossiter, Lauren M.; O'Connor, Abby R.; Chan, Benny C.
Graphical abstract: Transition metal complexes with 4-nitro- N -(quinolin-8-yl)benzenesulfonamide ligands were prepared and characterized by X-ray crystallography. Magnetic studies of 1-NO2 were reevaluated and show the complex to possess a Cu +2 metal center in solution and mixed Cu +2 and Cu +3 in the solid state. The electrochemistry of 1-NO2 supports redox activity for this ligand. Abstract: The coordination chemistry of 4-nitro- N -(quinolin-8-yl)benzenesulfonamide has been expanded. Crystal structures of bis[4- nitro - N -( quinolin -8- yl ) benzenesulfonamidato - κ 2 N, N ′]cobalt(II) (2 ), diaqua-bis[4- nitro - N -( quinolin -8- yl ) benzenesulfonamidato - κ 2 N, N ′]nickel(II) (3 ), and bis[4- nitro - N -( quinolin -8- yl ) benzenesulfonamidato - κ 2 N, N ′]zinc(II) (4 ) containing this ligand in ML2 stoichiometry were obtained. The nickel complex is isolated as a dihydrate. The degree of tetrahedrality for the four coordinate copper, cobalt, and zinc complexes was quantitatively compared by calculating the τ4 geometric parameters. Zinc complex 4 was found to be the most tetrahedral, while copper complex 1-NO2 deviated most from tetrahedral geometry. The magnetic moment calculated for 1-NO2 showed inconsistencies when measured in solution and in the solid state. Only a Cu +2 center exists in solution, while a possible mixed spin state of Cu +2 and Cu +3 is proposed in the solid state. With a more electron releasing substituent on the ligand of the copper complex as seen in complex 1-Me, this behavior is not observed and Cu +2 exists in solution and solid state. A reversible reduction at the same potential (−1.5 V vs. ferrocene) for both the ligand and the complex suggests possible redox activity of this class of ligand.